The therapeutic effects and applicability of the use of Cannabidiol in patients with Alzheimer's disease (Research, Society and Development, 2025)
Cannabis has been studied for its therapeutic potential, especially in the treatment of neurodegenerative diseases such as Alzheimer's, due to the neuroprotective, anti-inflammatory and antioxidant effects of cannabinoids. The endocannabinoid system, which includes CB1 and CB2 receptors, plays a crucial role in regulating physiological and behavioral functions. The objective of this research is to better understand the ability of cannabinoids to modulate this excitotoxic pathway, positioning them as potential therapeutic agents that can offer protection against the degenerative effects of AD.. The review followed ethical resolution no. 466/2012, using public domain data and was carried out in the MEDLINE/PubMed databases between January and March 2024. 52 articles were selected, of which 5 met the inclusion criteria, focusing on studies published between 2018 and 2024. These studies indicated that CBD has a positive impact on the treatment of the disease, helping to modulate pathological mechanisms and improving cognitive and neuropsychiatric symptoms. Among the approaches studied, cannabis was effective in relieving symptoms such as agitation and behavioral disorders, as well as benefits in rigidity and cognitive scores. CBD has shown protective effects against oxidative stress, and molecular modeling has suggested that compounds from Cannabis sativa may interact with therapeutic targets for Alzheimer's disease. Despite the positive results, the review highlights the need for more research and overcoming legal barriers to ensure the effectiveness and safety of medicinal cannabis in the treatment of Alzheimer's.